Integrated assessment of urban green infrastructure condition in Karlovo urban area by in-situ observations and remote sensing - Stelian Dimitrov; Georgi Georgiev; Margarita Georgieva; Maria Gluschkova; Ventsislava Chepisheva; Plamen Mirchev; Miglena Zhiyanski (One Ecosystem, 2018)
The knowledge about urban green infrastructure (UGI) is important for maintaining the quality of life in cities, suburbs and the fringes of metropolitan areas. The perspective of rapid urban sprawl generates the need for establishment and use of adequate systems for monitoring the condition of the urban ecosystems and green spaces. This triggers the search for a stronger link between the condition of urban green infrastructure and its capacity to supply ecosystem services (ES). In this paper are presented the results of the assessment of the health status of tree and shrub vegetation in UGI of Karlovo through an integrated application of in-situ observation and remote sensing using Unmanned Aerial Vehicle (UAV) technology. The study showed that the implementation of this flexible approach provides rapid and low-cost results, with good quality of the generated information. This makes the approach appropriate as a basis for monitoring of green systems in urbanised areas, with subsequent detailed investigation of solitary trees for cataclysms and epiphytotics of native species and rapid detection for the population of invasive insect and pathogen’s in order to prevent their distribution in new areas.